Green Roofs: a sustainable strategy - López-González, Brenda Guadalupe (2020)
The urbanization of the areas has brought benefits that have allowed economic growth and improvements in the quality of life of people, but has also paid for the environmental part. Green roofs are a technology that contributes to sustainable development. For this reason, the present work discloses relevant information about the origin, characteristics and benefits of green roofs, as well as a compilation of academic activities of different organisms being carried out in favor of this green technology and, finally, successful cases in Mexico. A series of environmental benefits are reported, such as the reduction of pollution and temperature of the environment, social benefits such as the reduction of diseases and mortality percentages in the population and economic benefits such as savings due to the reduction of energy consumption.